Clean and Healthy Living Behavior in the Taulotang Tribe Community in Sidenreng Rappang Regency - Mu'minun, Nona; Hatusupy, Chaterin Y; Nursiah, Andi; Nursinah, A.; P, Nur Triningtias; Akbar, Akbar (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The Taulotang tribe is one of the tribes that only exists in Sidrap district and has real cultural differences from other tribes in Sidrap district. Healthy and clean living behavior is a form of embodiment of the healthy paradigm in individual culture. This research aims to examine the healthy and clean living behavior of the Taulotang Tribe community in Sidrap Regency. This type of research is observational research. This research was carried out in Sidrap Regency. The research population was all 754 families, the research sample was 100 respondents, the sampling technique was simple random sampling and the data analysis used was descriptive analysis. The research results show that the majority are men over 50 years old, have low education and work as farmers. The behavior of using healthy latrines was 54%, 37% used unhealthy latrines, and 9% used poor latrines. The behavior of using clean water is 94% and the use of unclean water is 6%. The behavior of respondents in using trash cans was 37% and 63% did not use trash cans. The behavior of using trash cans, the majority do not use trash cans, namely 63 respondents (63%) and only 37 respondents (37%) who use trash cans. The lack of behavior in using healthy toilets and the lack of behavior in using trash bins is caused by the lack of awareness of respondents regarding healthy and clean living behavior, for this reason, integrated efforts are needed to promote healthy and clean living behavior.The Taulotang tribe is one of the tribes that only exists in Sidrap district and has real cultural differences from other tribes in Sidrap district. Healthy and clean living behavior is a form of embodiment of the healthy paradigm in individual culture. This research aims to examine the healthy and clean living behavior of the Taulotang Tribe community in Sidrap Regency. This type of research is observational research. This research was carried out in Sidrap Regency. The research population was all 754 families, the research sample was 100 respondents, the sampling technique was simple random sampling and the data analysis used was descriptive analysis. The research results show that the majority are men over 50 years old, have low education and work as farmers. The behavior of using healthy latrines was 54%, 37% used unhealthy latrines, and 9% used poor latrines. The behavior of using clean water is 94% and the use of unclean water is 6%. The behavior of respondents in using trash cans was 37% and 63% did not use trash cans. The behavior of using trash cans, the majority do not use trash cans, namely 63 respondents (63%) and only 37 respondents (37%) who use trash cans. The lack of behavior in using healthy toilets and the lack of behavior in using trash bins is caused by the lack of awareness of respondents regarding healthy and clean living behavior, for this reason, integrated efforts are needed to promote healthy and clean living behavior.